Decision support system for selection of the best faculty staff using the analytical hierarchy process (AHP) method - Titus Kristanto; Dahliar Ananda; Achmad Muzakki; Dewi Rahmawati; Riza Akhsani Setyo Prayoga (Institute of Computer Science (IOCS), 2023)
The Faculty of Information Technology and Business is one of the faculties at the Telkom Surabaya Institute of Technology. This faculty has four staff, namely Prasetya, Setyawan, Pertiwi, and Berliana. Every semester, faculty leaders (deans and deputy deans) evaluate faculty staff based on predetermined criteria to provide the best performance for the faculty in carrying out their duties and obligations. Assessment of faculty staff selection is based on criteria, namely service, discipline, commitment, and cooperation. The decision support system for selecting the best faculty staff uses the Analytical Hierarchy Process (AHP) method, where the decision-making process is based on an alternative assessment process based on predetermined criteria. Calculations using the AHP method are in the form of ranking the importance of each criterion and making recommendations for the best faculty staff, where the order of criteria starts with the criteria of service, cooperation, discipline, and commitment. Alternative matrix calculations yielded a score of 0.4963 for Prasetya, a score of 0.1893 for Setyawan, a score of 0.1873 for Pertiwi, and a score of 0.127 for Berliana, so that the best faculty staff recommendations were obtained by Prasetya with the highest score of 0.4963.